Examining the challenges of availability of Kiswahili teaching and learning resources and strategies for enhancing academic performance in Kiswahili in Alego Usonga Sub County, Kenya - James Ochieng Sika; Akanga Fredrick Ochieng (Indonesian Educational Research Journal, 2023)
This study explores the factors behind poor Kiswahili performance in selected schools within the Alego-Usonga Sub-County. Kiswahili is learned globally for diverse purposes, including research, travel in East and Central Africa, meeting foreign academic requirements, connecting with East African diaspora roots, and voluntary work. However, Kiswahili performance in K.C.S.E. has been consistently low, with a five-year mean score of 4.74 (equivalent to D+). The research investigates challenges related to the availability of Kiswahili teaching and learning resources and proposes strategies for academic improvement. A sample of 311 students, 15 teachers, and 15 principals was selected through appropriate methods. Findings indicate that most secondary schools have a low book ratio of 1:3, and all other resources scored poorly, with a mean of 2.92, highlighting resource inadequacy as a significant challenge. The study recommends implementing strategies like donations, fundraising, and parental involvement to enhance resource availability. In conclusion, it emphasizes the need for government and stakeholder collaboration to improve Kiswahili's performance as a subject in the Sub-County.